2018
DOI: 10.5815/ijmecs.2018.05.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Project-based Cooperative Studio Studies on the Basic Electronics Skills of Students’ Cooperative Learning and their Attitudes

Abstract: Abstract-Engineering education plays a prominent role in the development of technologies, society, nation, production, economy and employment. It is the art of applying scientific and mathematical principles, and experience to produce a technical product or system to meet out a specific need in the society. Based on the literature, it was thought that implementation of a cooperative project-based education on electricalelectronics engineering students could contribute to their basic engineering skills, their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Kits can help teach various subjects such as physics, chemistry, and computer science. Korkmaz (2018) , Zhan & Hsiao (2020) , and Kunduracıoğlu (2018) also confirmed the suitability of using Lego building blocks in the teaching process in their studies.…”
Section: Robotic Aidssupporting
confidence: 66%
“…Kits can help teach various subjects such as physics, chemistry, and computer science. Korkmaz (2018) , Zhan & Hsiao (2020) , and Kunduracıoğlu (2018) also confirmed the suitability of using Lego building blocks in the teaching process in their studies.…”
Section: Robotic Aidssupporting
confidence: 66%
“…• H6: AI has a positive effect on PBL • H7: AI has a positive effect on SE • H8: AI has a positive effect on AP In the related literature, PBL has been advocated for enhancing students' interest and attitudes towards learning and their curiosity to pursue further education [40]. Through the PBL approach, students are meaningfully engaged when trying to solve a problem by searching, analysing, evaluating and synthesising knowledge [39], [41].…”
Section: Fig 1 Conceptual Modelmentioning
confidence: 99%
“…A vast number of empirical studies that investigated the effectiveness of PBL in higher education settings indicated a positive association with improved students' motivation, engagement, achievement and overall academic performance [10], [13], [14], [28], [40], [46]- [48]. Bilgin et al [34] investigated the effects of the PBL method on undergraduate students' achievement and its association with their self-efficacy beliefs about science teaching and opinions about PBL.…”
Section: Fig 1 Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They added that social literacy is also termed as social competence but social literacy is more broad and subtle and is a complex process when talking about how it is acquired (11). Moreover, the conduct of the study is important in order to emphasize the factors affecting the literacy of a student in the school setting and to examine if literacy influences student engagement through their English Speaking skills [42][43][44][45][46][47][48][49][50][51].…”
Section: Introduction 11 Rationalementioning
confidence: 99%